Al-Islam and Kemuhammadiyahan Competency Exam Model at Universitas Muhammadiyah Parepare - Muhammad Nurmaallah; Ambo Asse; Muhammad Siri Dangnga; Wardah Hanafie Das (Edumaspul: Jurnal Pendidikan, 2023)
The most significant criterion for the success of the Al-Islam Kemuhammadiyahan course at Universitas Muhammadiyah Parepare is improvements in student behavior, attitudes, and mentality. The AIK test model created is not just for exams, but also as a motivator for pupils to replicate exemplary behavior in society. The purpose of this research is to look into the rise in student worship experience using the Al-Islam and Kemuhammadiyahan Competency Tests. This is a qualitative study, and the method employed is a phenomenological approach. This study took about 2 (two) months to complete, and it included observations, interviews, and written tests. According to the findings of this study, the AIK exam model at Universitas Muhammadiyah Parepare involves three levels of exams that students must pass: taharah, practical worship, and Muhammadiyah. If a participant is disqualified, he or she must attend guidance in the AIK Lab with a designated lecturer/instructor. This cycle is repeated until the student is declared to have passed all three phases of the exam and is awarded a graduation certificate